Cerebrotendinous Xanthomatosis, A Rare Metabolic Disease - Siddiqui, Mahmudur Rahman; Mahbub, Md Sahriar; Islam, Quazi Tarikul (Journal of Medicine, 2012)
Cerebrotendinous xanthomatosis (CTX) is a rare genetic lipid storage disease. CTX is characterised by childhood-onset cataract, adolescent to young adult-onset tendon xanthomas and adult-onset progressive neurological dysfunction (dementia, psychiatric disturbances, pyramidal and/or cerebellar signs and seizures). A 32-year-old male patient presented to us with the features of this rare genetic metabolic disorder. DOI: http://dx.doi.org/10.3329/jom.v13i1.8690 JOM 2012; 13(1): 92-93